Ethiopia Food System Transformation Pathway: Seqota Declaration Game Changing Solution - Sinamo Boltena, Sisay (2021)
Sisay Sinamo Boltena SPECIAL EVENT Funding Food System Transformation in Developing Countries: An example from Ethiopia UNFSS Side Event -- Co-organized by IFPRI, The Alliance of Bioversity International and CIAT, CGIAR SEP 24, 2021 - 08:00 AM TO 09:30 AM EDT